PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA PADA KONSUMEN PT CAPELLA DINAMIK NUSANTARA PEKANBARU - Sukriani, Nurul (Jurnal Daya Saing, 2018)
Abstract : This research was conducted for PT. Capella Dinamik Nusantara Pekanbaru, using the independent variable, to find out its influence on the purchase decision of the Honda brand motorcycle. The population in this study were all consumers who bought Honda brand motorcycles through official Honda dealers in Pekanbaru, namely PT. Capella Dinamik Nusantara directed 19,853 people, and this sample was 100 people, using accidental random sampling technique that is by giving questionnaires to consumers of Honda motorbike buyers at PT Capella Dinamik Nusantara which were met by researchers. The data was collected by questionnaire method by filling the conditions directly with the respondents. The data analysis technique used is multiple linear regression which is operated through the SPSS 16 for Windows program. The results showed that simultaneous and partial promotion variables and a significant analysis of the purchasing decisions of Honda brand motorcycles for consumers of PT Capella Dinamik Nusantara Pekanbaru.